Comparison of the Effectiveness of Learning Model Problem Posing with Quantum Learning TANDUR toward Students’ Understanding in Mathematics Concept - Muhammad Luqman Asy'ary; Afifah Mad Jais (Hipotenusa : Journal of Mathematical Society, 2021)
The purpose of this research is to know the effectiveness of the learning model Problem Posing type Post Solution Posing with Quantum Learning TANDUR type to understand the concept of mathematics on the integral material is not necessarily use three-teir multiple choice diagnostic test based E-Learning class XI MIPA students in SMA N 1 Bringin year Lesson 2019/2020. This research is a quantitative study of quasi-experimental experiments with the design of Posttest Only Control Group design. The samples in this study were students of grade XI MIPA 1 and XI MIPA 2 SMA N 1 Bringin. The instrument used in this study was about understanding the mathematical concept of Three-Teir Multiple Choice Diagnostic Test. The results of the study gained that the classifications of class-savvy category XI MIPA 1 have an average of 26.18% while the class XI MIPA 2 has an average of 21.47%. Thus, understanding the concept of class XI MIPA 1 is higher than the class XI MIPA 2. Then based on the results of the hypothesis test using an average similarity test with test-T scores obtained t-count =-0.00691 is between-2.02 ≤ t-table ≤ 2.02 which means that the effectiveness of implementation of learning model Problem Posing type Post Solution Posing same as the application of learning model of Quantum Learning TANDUR type towards understanding student mathematics concept.